Pembangunan Meter Maya Bagi Pengukuran Kabel Kuasa - Mustaffa, Marini (Universiti Sains Malaysia, 2006)
The main purpose of this project is to design and develop a current measurement device for underground cables. There are two parts which involved in the developing of this current measurement device for power cables including hardware installation and software development. The current sensor is build based on Hall Effect in the flowing current of the power cables. This current sensor can sense high current up to 50A. This sensor is rely on electromagnetic field strength which develop constantly changing voltage vary in the range between 0 to maximum reading of 5V. Output of this current sensor depends on the voltage produce to get the actual current from the cable. Output signal from the hardware part will be use as an input signal for software development part. A microprocessor system using microcontroller PIC 16F877 is developed to analyze and process the implemented data. Data send from hardware to software part is in the form of serial communication using RS 232 pin DB9 cable. The result from the processor will be displayed to user through monitor using Visual Basic Version 6.0 ( Microsoft Programming ) as application program and Hyper Terminal. Hyper Terminal is a testing program for serial data transmission from hardware to software. User can measure and takes current, voltage and power reading of cable based on this visual.